A highly bioactive bone extracellular matrix-biomimetic nanofibrous system with rapid angiogenesis promotes diabetic wound healing. Issue 35 (7th August 2017) - Gao, Wendong; Jin, Wanwan; Li, Yannan; Wan, Li; Wang, Chenggui; Lin, Cai; Chen, Xiaofeng; Lei, Bo; Mao, Cong
Abstract : BGN-containing CPB nanofibrous scaffolds with rapid angiogenesis promotes diabetic wound healing. Abstract : Treatment of diabetic wounds with a rapid healing performance remains a critical clinical challenge. An extracellular matrix (ECM)-biomimetic structure has shown promise in promoting tissue regeneration through a mediating cellular microenvironment. Herein, we report bone ECM-biomimetic cell-free nanofibrous scaffolds for enhancing healing in diabetic full-thickness wounds. This bioactive nanofibrous matrix was composed of ECM-componential collagen (Col, mimicking protein), polycaprolactone (PCL), and bioactive glass nanoparticles (BGNs, mimicking biological apatite) (CPB). The influence and mechanism of CPB on endothelial cell behaviors, angiogenic and healing abilities were investigated in a diabetic wound rat model. CPB significantly improved attachment and proliferation of endothelial cells, and upregulated the expression of the angiogenesis marker (CD31). In vivo, CPB also significantly enhanced the angiogenesis, through greatly upregulating the mRNA and protein expressions of Hif-1α, VEGF, Col1 and α-SMA. Furthermore, due to rapid angiogenesis, granulation tissue formation, collagen matrix remodeling and epidermis differentiation were accelerated in the CPB group, and as a result efficient diabetic wound healing was observed. Our results demonstrated that the cell-free bone-ECM-biomimetic BGN-based nanofibrous matrix could efficiently enhance blood tissue regeneration and diabetic wound healing without additional growth factors. Our biomimetic materials system may also be suitable for other blood vessel-related tissue repair and regeneration processes.